2017
DOI: 10.1097/ccm.0000000000002026
|View full text |Cite
|
Sign up to set email alerts
|

Rural Patients With Severe Sepsis or Septic Shock Who Bypass Rural Hospitals Have Increased Mortality: An Instrumental Variables Approach*

Abstract: Objective To identify factors associated with rural sepsis patients’ bypassing rural emergency departments (EDs) to seek emergency care in larger hospitals, and to measure the association between rural hospital bypass and sepsis survival. Design, Setting, and Patients Cohort study of adults treated in EDs of a rural Midwestern state with severe sepsis or septic shock between 2005 and 2014, using administrative claims data. Patients residing ≥ 20 miles from a top-decile sepsis volume hospital and < 20 miles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…The quality of early sepsis management in rural EDs is critical, as over 40% of all US EDs are in rural counties 8 and delays in early care are associated with worse outcomes. 20,21 Rural hospital bypass and interfacility transfer both are associated with increased sepsis mortality, 22 and transfer is associated with low adherence with national sepsis resuscitation guidelines. 10,22 This study expands the field of rural sepsis care research by being the first to examine compliance with national sepsis guidelines between rural and urban EDs/ hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of early sepsis management in rural EDs is critical, as over 40% of all US EDs are in rural counties 8 and delays in early care are associated with worse outcomes. 20,21 Rural hospital bypass and interfacility transfer both are associated with increased sepsis mortality, 22 and transfer is associated with low adherence with national sepsis resuscitation guidelines. 10,22 This study expands the field of rural sepsis care research by being the first to examine compliance with national sepsis guidelines between rural and urban EDs/ hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Rural hospital bypass and interfacility transfer both are associated with increased sepsis mortality, 22 and transfer is associated with low adherence with national sepsis resuscitation guidelines. 10,22 This study expands the field of rural sepsis care research by being the first to examine compliance with national sepsis guidelines between rural and urban EDs/ hospitals. Literature on rural health care quality is scarce as rural hospitals are traditionally exempted or excluded from quality reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the increasing trend toward rural hospital bypass may be putting patients with timesensitive conditions at greater risk of hospital death due to delays in care related to transportation. 32 Alternatively, this could suggest lower quality of care at urban hospitals. Future work is needed to fully evaluate these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Furthermore, when patients bypass local hospitals and directly present to tertiary care, mortality for time-sensitive illnesses, such as sepsis, increases. 3 Unfortunately, although critical access hospitals (CAHs) had an equivalent risk-adjusted mortality in 2002, they have failed to improve their performance at the same rate as that of larger hospitals and lag in quality metrics. 4,5 One potential contributor to the lagging performance may be the low uptake of the hospitalist model at these facilities.…”
mentioning
confidence: 99%